Moringa oleifera L. Extracts as Bioactive Ingredients That Increase Safety of Body Wash Cosmetics - Zofia Nizioł-Łukaszewska; Dominika Furman-Toczek; Tomasz Bujak; Tomasz Wasilewski; Zofia Hordyjewicz-Baran (Dermatology Research and Practice)
The work attempts to obtain a multifunctional plant extract derived from Moringa tree leaves. Obtained results indicate a strong antioxidant potential of the tested extracts. It was shown that Moringa oleifera leaf extract is a rich source of flavonoid and phenolic compounds. Furthermore, it shows a strong antioxidant activity by scavenging free radicals. In vitro toxicity studies showed that the tested extracts in concentrations up to 5% showed a positive effect on cell proliferation and metabolism and may contribute to the reduction of oxidative stress in cells. It was noted that the tested model formulation of cosmetic (1% SCS) with the addition of different types of extracts might contribute to the reduction of skin irritation and improve the safety of the product.